Synthesis and mechanical properties of Bi2O3-Al4Bi2O9 nanopowders - Askari, Shayan; Ghashang, Majid; Sohrabi, Ghazal (Journal of Composites and Compounds, 2020)
As a result of great surface area and a great number of energetic sites, ceramic nanocomposites are being considered as good adsorbents and catalysts. Al2O3 nanoparticles are widely used in high-tech applications owing to their excellent properties. Besides, Bi-based oxides have been the center of attention for applications such as remediation of hazardous wastes and wastewater photochemical degradation of organic contaminants and remediation of hazardous wastes. In this research, the synthesis of Bi2O3-Al4Bi2O9 nanocomposite and its mechanical properties as a novel composition were investigated. The results showed that the prepared Bi2O3-Al4Bi2O9 sample exhibited the Al4Bi2O9 crystalline peaks. Additionally, the prepared nanocomposite showed no impurities. The mechanical properties of the Bi2O3-Al4Bi2O9 sample were improved in comparison with Al2O3, Bi2O3, and Bi2O3- Al2O3, which offer it as a promising alternative to Bi2O3-Al2O3 composite ceramic.